Animal production and antimicrobial resistance in the clinic - Robinson, Timothy P.; Wertheim, H.F.L.; Kakkar, M.; Kariuki, S.; Bu, D.; Price, L.B. (Elsevier, 2016)
One of the major public health challenges this century is the development of antimicrobial resistance in many important and common pathogens, such as Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. The Lancet Series on antimicrobials tackles the issue head-on by presenting evidence on universal access to antibiotics, sustainability, and effectiveness.The Series focuses on the use and misuse of antimicrobials in human medicine but does not ignore other sources of antimicrobial resistance development: waste and contamination from the pharmaceutical industry, animal agriculture, and the natural arms race that has been fought among microbes in the environment since the dawn of evolution.